Willoq: un caso de turismo vivencial - Abarca, Alfredo (2005)
The Willoq community and Peruvian Odyssey have joined efforts in order to bring the everyday life of the high Andean communities in the area of Ollantaytambo closer to tourists. This is known as «existential tourism», and has as a basic premise the preservation of the Andean Man’s customs and traditions. Perhaps the magic and charm experienced by those who visit the Willoq community resides in the vast and diverse landscape in front of them, as well as in the various cultural manifestations that are so different to theirs in terms of: organization, economy, religion, and a sustainable interaction through time with the environment. But we can also see the crude reality and difficulties of the Willoq community, as well as the illusion and hope with which they view an ever more globalized world.